Review of the grassland leafhopper genus Nephotettix Matsumura (Hemiptera: Cicadellidae: Deltocephalinae: Chiasmini) from the Chinese mainland - Duan, Yani; Zhang, Yalin (Zootaxa, 2014)
The Chinese mainland species of the leafhopper genus Nephotettix Matsumura (Hemiptera: Cicadellidae: Deltocephalinae: Chiasmini) (Nephotettix cincticeps (Uhler), Nephotettix malayanus Ishihara & Kawase, Nephotettix nigropictus (Stål), Nephotettix parvus Ishihara & Kawase rec. n., and Nephotettix virescens (Distant)) are reviewed. This genus is redescribed. Variation is described and illustrated. Keys for their separation are provided together with a worldwide checklist.